Особливості оранжерейної культури Paphiopedilum insigne (Wall. ex Lindl.) Pfitz. (Orchidaceae Juss.) - Vakhrushkin, V.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 1999)
The features of development of both adult plants and seedlings of Paphiopedilum insigne (Wall. ex Lindl.) Pfitz. under greenhouse culture conditions were studied. The technology of cultivation (soil mixture, temperature, nutrition) of plant was elaborated. The particular attention is given to undestanding of relation between the growth of plant under greenhouse conditions and ecology of natural habitats.